Kelayakan Media Buku Saku Sistem Endokrin di Kelas XI SMA - Novitasari Novitasari; Ruqiah Ganda Putri Panjaitan; Eko Sri Wahyuni (Faculty of Teacher Training and Education, Musamus University, 2021)
The research purposed to determine the feasibility of pocket book as a learning media on the sub-material endocrine system in Senior High School grade XIth. This research used a descriptive method with a survey research form. The research instrument used a validation sheet consisting of 3 aspects including the format, content, and language aspects which were validated by 5 validators. Assessment of the validation sheet used a Likert scale and data analysis is based on Lawshe (1975). Based on the results of the study, it shows that the format aspect gets a CVR value of 1 in the valid category, the content aspect gets a CVR value of 1 in the valid category, and the language aspect gets a CVR value of 1 with the valid category. Overall, the data from the validation results of pocket book media get a Content Validity Index (CVI) value of 1.00 > 0.99 so that the pocket book media is valid and suitable for use as a learning media for the sub-material endocrine system in Senior High School grade XIth